Korke: Rumah Moderasi Beragama Masyarakat Lamaholot di Flores Timur - Anselmus Dorewoho Atasoge; Alfonsus Mudi Aran; Adison Adrianus Sihombing (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2023)
Local wisdom has an important position as a pillar of building religious moderation. This study explored the function and the meaning of korke, the traditional house of Lamaholot tribe, in East Flores, as an effort to ground religious moderation. The purpose of this study is included the concept of Korke by the Lamaholot people and the effects on the people’s lifestyle and relationship pattern as well as the implication of korke on religious harmony in Indonesia, specifically in East Flores. The qualitative method was employed in this study to support the study objective. Observation, interview, and documentation study were selected as the data collection technique. The data were collected from May2022 to August 2022. This study with fucntionalisme structural perspective found that Lamaholot people with different religious backgrounds used the Korke as a public house and consider themselves who were born from the same and the only mother and father. In the korke, the conflict needed a solution to solve the problem, and therefore harmonious relationships can come to life again. This is the starting point for efforts to build religious moderation and enriches to a study on local wisdom and religious phenomena.